2021
DOI: 10.1126/scitranslmed.abb2639
|View full text |Cite
|
Sign up to set email alerts
|

Antibody semorinemab reduces tau pathology in a transgenic mouse model and engages tau in patients with Alzheimer’s disease

Abstract: Tau has become an attractive alternative target for passive immunotherapy efforts for Alzheimer’s disease (AD). The anatomical distribution and extent of tau pathology correlate with disease course and severity better than other disease markers to date. We describe here the generation, preclinical characterization, and phase 1 clinical characterization of semorinemab, a humanized anti-tau monoclonal antibody with an immunoglobulin G4 (igG4) isotype backbone. Semorinemab binds all six human tau isoforms and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 66 publications
4
46
0
Order By: Relevance
“…Preliminary findings from phase I trial indicated that the treatment is tolerable and safe, but was not efficiently immunogenic; therefore, a second-generation vaccine, ACI-35.030, has been generated. ACI-35.030 is 5 times more immunogenic than its predecessor and will replace ACI-35 in the phase I/II safety and tolerability clinical trial ( 183 ).…”
Section: Results: Therapeutic Strategies Targeting Neuroinflammation In the Management Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…Preliminary findings from phase I trial indicated that the treatment is tolerable and safe, but was not efficiently immunogenic; therefore, a second-generation vaccine, ACI-35.030, has been generated. ACI-35.030 is 5 times more immunogenic than its predecessor and will replace ACI-35 in the phase I/II safety and tolerability clinical trial ( 183 ).…”
Section: Results: Therapeutic Strategies Targeting Neuroinflammation In the Management Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…Tau has been an important target in therapeutics development for AD and primary tauopathies. Immunotherapies semorinemab, gosuranemab (Boxer et al, 2019;Ayalon et al, 2021;Grossman, 2021;Mullard, 2021;Novak et al, 2021), antisense oligonucleotides (DeVos et al, 2017), and aggregation inhibitors are at different stages of clinical trials (Congdon and Sigurdsson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic animal models recapitulating human tauopathy have enabled understanding of disease mechanisms and facilitated the development of treatment strategies ( Albert et al, 2019;Roberts et al, 2020;Ayalon et al, 2021). Varieties of transgenic mouse lines with mutations on MAPT gene including P301S (PS19), P301L (JNPL3, rTg4510, pR5) ( Lewis et al, 2000;Ramsden et al, 2005;Santacruz et al, 2005;Yoshiyama et al, 2007;de Calignon et al, 2012), knock-out hTau (Andorfer et al, 2003), and knockin (Hashimoto et al, 2019;Saito et al, 2019) mouse models as well as transgenic rat models (Filipcik et al, 2012) have been developed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations